(untitled) - Dunleavy, Patrick (New York, 2003)
Authoring a PhDinvolves having creative ideas, working out how to organize them, writing up from plans, upgrading text, and finishing it speedily and to a good standard. It also involves being examined and getting work published. This book provides a huge range of ideas and suggestions to help PhD candidates cope with both the intellectual issues involved and the practical difficulties of organizing their work effectively.
Keywords: Dissertations, Academic,Academic writing; Authorship,Handbooks, manuals, etc.,Handbooks, manuals, etc